Fatores influenciadores no processo de internacionalização: um estudo em empresas gaúchas do setor de máquinas e equipamentos - Silva, Vanessa Almeida da (2011)
This article develops the theme of internationalization of micro, small and medium enterprises in New South Wales and aims to relate institutional factors and the chara cteristics of entrepreneurial behavior that affect this process. In addition, we sought to describe the profile, to characterize the international operations, verify the institutional factors and identify the characteristics of resilient people of entrepre neurial companies surveyed. To this end, we reviewed issues related to the internationalization of business, international entrepreneurship, modes of entry, approach and institutional isomorphism in order to guide empirical research. Descriptive research w as conducted with application of a procedure for collecting survey data on which were analyzed using only descriptive statistical technique, due to limitations of the study. The results showed that the surveyed companies are distributed among micro, small and medium - sized and fit into the international market, mainly by way of export. It was identified that over half of the respondents answers to 05 countries and practiced international activities for 15 years. The main reasons were cited for internationali zation intent to internationalize itself since the beginning of its operations, developing skills to work abroad and the existence of client request coming from abroad. Another important aspect of our study refers to institutional factors, which highlight the statements that managers tended to a substantial similarity between the competitors who attended the international market, demonstrating the mimetic isomorphism. Furthermore, we observed that internationalization has generated positive impacts, conside ring the added value in terms of performance and control activities. Much of respondents' political mobilization begins among interest groups, intended to build coalitions with other actors in order to obtain resources and approvals. The data related to in ternational entrepreneurship demonstrated that entrepreneurial behavior is a recurring element to characterize the internationalization and, through the concept of resilience in the process of analyzing this study, the results highlighted the element of po sitivity. The study had some limitations, resulting in the number of companies surveyed, making it impossible to develop multivariate statistical analysis, which ignore the minimum number of individuals. However, it is remarkable that the institutional fac tors influencing international and entrepreneurial companies in their internationalization process because it stimulates innovation and contributes to the mimicry, positivity and adaptability to changes